2000
DOI: 10.1002/(sici)1097-0347(200003)22:2<149::aid-hed6>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arachidonic acid metabolites in a murine model of squamous cell carcinoma

Abstract: Background A murine model (C3H mice) of squamous cell carcinoma (SCCVII) has been used to investigate the role of arachidonic acid (AA) metabolites in head and neck cancer. Inhibition of tumor growth by cyclooxygenase (COX) and lipoxygenase (LOX) inhibitors of AA metabolism has been associated with changes in levels of AA metabolites in tumor tissues and inflammatory cell infiltrates. To characterize this model further, the effects of exogenous AA metabolites on tumor growth in vitro and in vivo were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…A study by Tanaka et al [37] involving rats with precancerous lesions of the tongue revealed that the incidence of HNSCC was reduced to 23%–31% with the administration of NSAIDs compared to 71% in rats that did not receive NSAIDs. Laboratory studies have also shown that NSAIDs increase the host immune cell infiltration in tumor cells [38], inhibit the growth of squamous cell cancer in mice [3941], and cultured human HNSCC cell lines [42]. There has also been immunohistochemical evidence indicating that the expression of COX-2 protein in oral mucosal lesions increases as the lesions progress from hyperplasia to dysplasia with the highest levels of COX-2 stain found in SCC.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tanaka et al [37] involving rats with precancerous lesions of the tongue revealed that the incidence of HNSCC was reduced to 23%–31% with the administration of NSAIDs compared to 71% in rats that did not receive NSAIDs. Laboratory studies have also shown that NSAIDs increase the host immune cell infiltration in tumor cells [38], inhibit the growth of squamous cell cancer in mice [3941], and cultured human HNSCC cell lines [42]. There has also been immunohistochemical evidence indicating that the expression of COX-2 protein in oral mucosal lesions increases as the lesions progress from hyperplasia to dysplasia with the highest levels of COX-2 stain found in SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that indeed a combination of PUFAs and conventional anti-cancer drugs have more potent action on tumor cells compared to either compound alone [18] – [23] . Some studies suggested that the tumoricidal action of PUFAs is not dependent on the formation of cyclo-oxygenase (COX) and lipoxygenase (LOX) products though, this has been disputed [1] , [2] , [24] [28] . This uncertainty of the involvement of COX and LOX products on the growth/apoptosis of tumor cells is further supported by the observation that different prostaglandins either enhance or inhibit growth depending on the dose and type of the compounds tested and much less is known about the action of leukotrienes and thromboxanes on cancer cells [29] – [42] .…”
Section: Introductionmentioning
confidence: 99%
“…10 Although, multiple enzymes related to eicosanoid metabolism are similar in terms of structure, substrate preference and mechanisms of action, a variety of biological effects have been demonstrated for their products in various experimental models. [11][12][13][14] In fact, elevated PG levels have been detected in HNSCC cell lines and neoplastic tissues resected from patients. [15][16][17] Furthermore, there is evidence for a strong correlation between PGE 2 synthesis and prognostic significance as well as metastatic ability of tumor cells in vivo, 18,19 Accordingly, COX-2 isoenzyme is frequently upregulated in HN cancers that have been reported to be associated with tumor growth, resistance to apoptosis, metastasis, and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%